2017
DOI: 10.3390/bs7010010
|View full text |Cite
|
Sign up to set email alerts
|

Early Maladaptive Schemas and Cognitive Distortions in Adults with Morbid Obesity: Relationships with Mental Health Status

Abstract: Dysfunctional cognitions may be associated with unhealthy eating behaviors seen in individuals with obesity. However, dysfunctional cognitions commonly occur in individuals with poor mental health independently of weight. We examined whether individuals with morbid obesity differed with regard to dysfunctional cognitions when compared to individuals of normal weight, when mental health status was controlled for. 111 participants—53 with morbid obesity and 58 of normal weight—were assessed with the Mini-Mental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…Our results also showed that binge eating severity was positively associated with three maladaptive schemas (i.e., disconnection/rejection, impaired limits, and other-directedness domains). No significant association was observed between BMI and EMSs scores, suggesting that dysfunctional schemas in overweight and obese women are likely related to their individual mental health (i.e., dysfunctional eating patterns and/or psychopathology) and not to their weight, as has been previously hypothesized for patients with morbid obesity [ 30 ]. Finally, our regression analysis showed that the disconnection/rejection schema score was independently associated with FA symptoms, after controlling for the presence of other potential confounding variables (e.g., psychopathology and binge eating severity), suggesting that this domain may be a crucial factor for the development of FA.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Our results also showed that binge eating severity was positively associated with three maladaptive schemas (i.e., disconnection/rejection, impaired limits, and other-directedness domains). No significant association was observed between BMI and EMSs scores, suggesting that dysfunctional schemas in overweight and obese women are likely related to their individual mental health (i.e., dysfunctional eating patterns and/or psychopathology) and not to their weight, as has been previously hypothesized for patients with morbid obesity [ 30 ]. Finally, our regression analysis showed that the disconnection/rejection schema score was independently associated with FA symptoms, after controlling for the presence of other potential confounding variables (e.g., psychopathology and binge eating severity), suggesting that this domain may be a crucial factor for the development of FA.…”
Section: Discussionmentioning
confidence: 89%
“…Poursharifi et al [ 29 ] reported that some aspects of identity (e.g., social and relational identities) were positively associated with EMSs in obese patients. More recently, da Luz et al [ 30 ] observed that, compared to normal-weight individuals, patients with morbid obesity (BMI > 40 kg/m 2 ) had higher scores for the insufficient self-control/self-discipline schema, even though this difference was not significant when mental health status was controlled for. Finally, it has been reported that, compared to normal-weight adolescents, overweight [ 31 ] and obese [ 32 ] adolescents reported higher EMSs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies [15, 26, 27, 28, 29, 30, 31] have shown an association between early maladaptive schemas (i.e., abandonment, insufficient self-control social isolation, failure to achieve, defectiveness/ shame, dependence/ incompetence, entitlement/ grandiosity) and overeating, and other eating-related dysfunctional attitudes, such as food addiction and bingeing. Similarly, in our study overweight/obese participants reported more intense abandonment, dependence, subjugation and insufficient-self control schemas, compared with normal weight subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the present results on the quality of interpersonal relationships, studies showed that individuals with obesity reported elevated interpersonal distress (e.g., Lo Coco et al, 2012 ). Some studies reported the presence of maladaptive schemata related to social isolation, shame, and failure to achieve and an association between overeating and early maladaptive schemas ( Anderson et al, 2006 ; Da Luz et al, 2017 ; Imperatori et al, 2017 ). Specifically, a recent study showed that individuals with overweight and obesity reported more intense abandonment, dependence, subjugation, and insufficient self-control schemas, compared with normal-weight subjects ( Basile et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%